2019
DOI: 10.1103/physrevc.99.054325
|View full text |Cite
|
Sign up to set email alerts
|

Shape coexistence in Hg178

Abstract: Lifetime measurements of excited states in 178 Hg have been performed using the 103 Rh(78 Kr, p2n) reaction at a beam energy of 354 MeV. The recoil-decay tagging (RDT) technique was applied to select the 178 Hg nuclei and associate the prompt γ rays with the correlated characteristic ground-state α decay. Lifetimes of the four lowest yrast states of 178 Hg have been determined using the recoil distance Doppler-shift (RDDS) method. The experimental data are compared to theoretical predictions with focus on shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Yang et al [76] found that the degenerate minima are more related to quadrupole deformation than triaxial deformation. Many experiments have been carried out to discover shape coexistence in nuclei, for example, see [27,29,[77][78][79][80] for Hg isotopes.…”
Section: Shape Coexistencementioning
confidence: 99%
“…Yang et al [76] found that the degenerate minima are more related to quadrupole deformation than triaxial deformation. Many experiments have been carried out to discover shape coexistence in nuclei, for example, see [27,29,[77][78][79][80] for Hg isotopes.…”
Section: Shape Coexistencementioning
confidence: 99%
“…Further information on collective structures in neutron-deficient Hg nuclei was provided by measurements of γ-ray transition strengths. Lifetimes of excited states were measured for several neutron-deficient species, populated via fusion-evaporation reactions: the 178 Hg [21], 180,182 Hg [22,23] and 184,186 Hg [16,24,25] nuclei were studied using the Recoil-Distance Doppler-Shift (RDDS) method, while the Doppler-Shift Attenuation Method (DSAM) and the β-tagged fast-timing (FT) techniques were employed to investigate the 184 Hg [26] and 186,188 Hg [14,27] isotopes, respectively. Moreover, the lifetimes of low-lying states in 190−196 Hg isotopes, which could not be obtained via RDDS method due to the presence of low-lying isomers, were recently measured via the FT technique [27,28].…”
Section: Charge Radius [Fm]mentioning
confidence: 99%
“…Further information on collective structures in neutrondeficient Hg nuclei was provided by measurements of γray transition strengths. Lifetimes of excited states were measured for several neutron-deficient species, populated via fusion-evaporation reactions: the 178 Hg [21], 180,182 Hg [22,23], and 184,186 Hg [16,24,25] nuclei were studied using the recoil-distance Doppler-shift (RDDS) method, while the Doppler-shift attenuation method (DSAM) and the β-tagged fast-timing (FT) techniques were employed to investigate the 184 Hg [26] and 186,188 Hg [14,27] isotopes, respectively. Moreover, the lifetimes of low-lying states in [190][191][192][193][194][195][196] Hg isotopes, which could not be obtained via RDDS method due to the presence of low-lying isomers, were recently measured via the FT technique [27,28].…”
Section: Introductionmentioning
confidence: 99%